The Use of PowerPoint and Video as Learning Media in Online Learning and Physics Learning Outcomes in High School - Fitria Hatiku; Masri Kudrat Umar; Supartin Supartin; Muhammad Yusuf; Abdul Haris Odja; Citron S. Payu (Department of Physics Education, Universitas Mataram, 2022)
This study aims to discover and see how power points and videos are used during online learning as well as its effects on student learning outcomes in online learning on light wave material in class XI Science SMA Negeri 1 Bongomeme, SMA Negeri 1 Dungaliyo and SMA Negeri 1 Tibawa. The research method used is descriptive quantitative. The research subjects were 283 students of class XI science. Data collection techniques used were questionnaires and learning outcome tests. The data analysis technique used were descriptive and quantitative analysis. The results of this study indicate that, based on their respective indicators, the use of power points and films/videos in online learning obtain a percentage value of 80.25% and 79.97% respectively, both of which are included within the criteria of strong. On average, the student learning outcomes in three schools are above minimum require score (KKM) of 75. Here, the average value of student learning outcomes at SMA Negeri 1 Bongomeme 77.52, SMA Negeri 1 Dungaliyo 79.18, SMA Negeri 1 Tibawa is 80.91.